The Influence of Family Interaction on Early Childhood Independence - Mohzana Mohzana; Hary Murcahyanto (Sumber Belajar Sejahtera, 2023)
The purpose of this study was to determine the effect of interaction in the family on the independence of early childhood. The type of research used in this study is a type of quantitative research using the experimental method. The research design used is a pre-experimental design in the form of a One-Group pretest-posttest design. The subjects of this study were the entire group B of the Islamic Kindergarten, totaling 15 children. The instruments used to collect data are validation sheets, observation sheets, and documentation. The results showed that children's independence during the pre-test amounted to 214 with an average percentage of 31% and in the category of assessment Starting to Develop (MB) and after being given treatment or (treatment) then held a posttest obtained the independence of all children, namely 585 with an average of 97% and the assessment category Developing Very Well (BSB). In addition, it can also be seen from the results of the hypothesis test t-count ≥ t-table difference (7.3131) ≥ (2.145) at a significant level of 0.05 so it can be concluded that Ha is accepted and Ho is rejected, so between the pre-test and post-test results are significant.